2022
DOI: 10.1161/strokeaha.121.036885
|View full text |Cite
|
Sign up to set email alerts
|

Review of Long-Term Blood Pressure Control After Intracerebral Hemorrhage: Challenges and Opportunities

Abstract: Blood pressure (BP) is the most important modifiable risk factor for intracerebral hemorrhage (ICH). Elevated BP is associated with an increased risk of ICH, worse outcome after ICH, and in survivors, higher risks of recurrent ICH, ischemic stroke, myocardial infarction, and cognitive impairment/dementia. As intensive BP control probably improves the chances of recovery from acute ICH, the early use of intravenous or oral medications to achieve a systolic BP goal of <140 mm Hg within the first few hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 112 publications
0
12
0
Order By: Relevance
“…In the majority of ICH survivors, blood pressure remains the most important modifiable risk factor. As Mullen and Anderson 4 summarize in this Focused Update, elevated blood pressure is associated with a continuum of central nervous system and systemic events after an ICH. Blood pressure control is often categorized in terms of the acute emergency or inpatient management and the chronic or outpatient component.…”
Section: Blood Pressure Control After Ichmentioning
confidence: 97%
“…In the majority of ICH survivors, blood pressure remains the most important modifiable risk factor. As Mullen and Anderson 4 summarize in this Focused Update, elevated blood pressure is associated with a continuum of central nervous system and systemic events after an ICH. Blood pressure control is often categorized in terms of the acute emergency or inpatient management and the chronic or outpatient component.…”
Section: Blood Pressure Control After Ichmentioning
confidence: 97%
“…BP-lowering also reduces the risk of ischaemic events and might mitigate the progression of cerebral small vessel disease which contributes to the delayed cognitive impairment and dementia that follow ICH. 24 The Perindopril Protection Against Recurrent Stroke Study (PROGRESS) study and subsequent post-hoc analyses showed that patients with the lowest BP levels during follow-up had the lowest risk of stroke recurrence, both ischaemic and haemorrhagic ones. Strong relationship was found between lower SBP levels and haemorrhagic stroke (P homogeneity = 0.003) with a relative risk reduction of 49% (95% CI, 18%-68%).…”
Section: Blood Pressure Loweringmentioning
confidence: 99%
“…33 BP levels should be assessed regularly in all patients regardless of age, location or presumed small vessel disease underlying the acute ICH. 24 Solid evidence suggests that antiplatelet resumption is safe in the majority of patients with ICH. 34,35 The RESTART trial (Restart or Stop Antithrombotics Randomized Trial) is the only randomized controlled trial that compared the effects of starting or avoiding antiplatelet therapy after ICH.…”
Section: Blood Pressure Loweringmentioning
confidence: 99%
See 2 more Smart Citations